2019
DOI: 10.1002/pri.1824
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic spine manipulation did not improve maximal mouth opening in participants with temporomandibular dysfunction

Abstract: Background and Purpose Temporomandibular joint disorders (TMD) have a prevalence of more than 5% in the general population. A positive correlation exists between temporomandibular joint mobility and cervical spine mobility. Similarly, a relationship exists between thoracic and cervical spine mobility. However, it is unknown if interventions to improve the mobility of the thoracic spine positively impact temporomandibular joint motion and pain. This study tested the hypothesis that a single thoracic thrust join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Joint position sense was reported in five studies. Two studies reported increased joint position error in TMD groups compared with controls, while two studies found no significant difference 56 Mod Lafreniere et al 1997 57 Mod MazzeƩo et al 2017 34 Mod Miller et al 1999 81 Mod Miller et al 2000 58 Mod Monteiro et al 1987 59 Mod PiƩa et al 2015 37 Mod Pizolato et al 2007 38 Mod Rauch et al 2018 39 Mod Rezaie et al 2017 40 Mod Seligman et al 1988 61 Mod Stegenga et al 1990 62 Mod Thorp et al 2019 67 Mod Todic et al 2019 70 Mod Tsolka et al 1994 71 Mod Turp et al 2005 43 Mod Visser et al 1995 63 Mod Wang et al 2018 72 Mod Xu et al 2017 44 Mod Zhang et al 2017 64 Mod Badel et al 2011 19 High Dahlstrom et al 1989 50 High Dworkin et al 1990 52 High Goulet et al 1998 77 High Isacsson et al 1988 54 High Lindauer et al 1986 80 High Nielsen et al 1990 60 High Nielsen et al 1987 78 High Van Willigen et al 1986 82 High 61 Reduced in all TMD groups compared to assymptomatic controls (P < .001 all except DDwR where P < .05). Reduced in all TMD groups, except DDwR, compared to symptomatic controls (P < .001)…”
Section: Tmj Proprioceptionmentioning
confidence: 99%
“…Joint position sense was reported in five studies. Two studies reported increased joint position error in TMD groups compared with controls, while two studies found no significant difference 56 Mod Lafreniere et al 1997 57 Mod MazzeƩo et al 2017 34 Mod Miller et al 1999 81 Mod Miller et al 2000 58 Mod Monteiro et al 1987 59 Mod PiƩa et al 2015 37 Mod Pizolato et al 2007 38 Mod Rauch et al 2018 39 Mod Rezaie et al 2017 40 Mod Seligman et al 1988 61 Mod Stegenga et al 1990 62 Mod Thorp et al 2019 67 Mod Todic et al 2019 70 Mod Tsolka et al 1994 71 Mod Turp et al 2005 43 Mod Visser et al 1995 63 Mod Wang et al 2018 72 Mod Xu et al 2017 44 Mod Zhang et al 2017 64 Mod Badel et al 2011 19 High Dahlstrom et al 1989 50 High Dworkin et al 1990 52 High Goulet et al 1998 77 High Isacsson et al 1988 54 High Lindauer et al 1986 80 High Nielsen et al 1990 60 High Nielsen et al 1987 78 High Van Willigen et al 1986 82 High 61 Reduced in all TMD groups compared to assymptomatic controls (P < .001 all except DDwR where P < .05). Reduced in all TMD groups, except DDwR, compared to symptomatic controls (P < .001)…”
Section: Tmj Proprioceptionmentioning
confidence: 99%
“…Another randomized controlled trial that investigated the effects of adding cervical spinal manipulation to standard care for TMD also found that cervical spinal manipulation had better outcomes in improving TMD-associated pain, mouth opening, disability, fear avoidance, and global perceived effect [ 14 ]. However, a previous study found that thoracic spinal manipulation does not affect TMD [ 15 ]. As the previous case report found relief of atypical symptoms with correction of cervical and thoracic curvature [ 16 ], the chiropractor decided to provide the treatment to both cervical and thoracic correction to reach the maximum outcome.…”
Section: Discussionmentioning
confidence: 99%